Natural Lakes Are a Minor Global Source of N2O to the Atmosphere. Issue 12 (6th December 2019) - Lauerwald, R.; Regnier, P.; Figueiredo, V.; Enrich‐Prast, A.; Bastviken, D.; Lehner, B.; Maavara, T.; Raymond, P.
Abstract: Natural lakes and reservoirs are important yet not well‐constrained sources of greenhouse gasses to the atmosphere. In particular for N2 O emissions, a huge variability is observed in the few, observation‐driven flux estimates that have been published so far. Recently, a process‐based, spatially explicit model has been used to estimate global N2 O emissions from more than 6, 000 reservoirs based on nitrogen (N) and phosphorous inflows and water residence time. Here we extend the model to a data set of 1.4 million standing water bodies comprising natural lakes and reservoirs. For validation, we normalized the simulated N2 O emissions by the surface area of each water body and compared them against regional averages of N2 O emission rates taken from the literature or estimated based on observed N2 O concentrations. We estimate that natural lakes and reservoirs together emit 4.5 ± 2.9 Gmol N2 O‐N year −1 globally. Our global‐scale estimate falls in the far lower end of existing, observation‐driven estimates. Natural lakes contribute only about half of this flux, although they contribute 91% of the total surface area of standing water bodies. Hence, the mean N2 O emission rates per surface area are substantially lower for natural lakes than for reservoirs with 0.8 ± 0.5 versus 9.6 ± 6.0 mmol N·m −2 ·year −1, respectively. This finding can be explained by on average lower external N inputs to natural lakes. We conclude that upscaling‐based estimates, which do not distinguish natural lakes from reservoirs, are prone to important biases. Key Points: Global N2 O emission from natural lakes and reservoirs estimated at 4.5 ± 2.9 Gmol N year ‐1 Natural lakes emit less N2 O than reservoirs North America and Europe contribute nearly half of global N2 O emission from natural lakes and reservoirs